STUDI PENGARUH VARIASI BENTUK WAVE-PIERCING TERHADAP HAMBATAN PADA HIGH SPEED CRAFT (HSC) BERLAMBUNG KATAMARAN DENGAN SIMULASI COMPUTATIONAL FLUID DYNAMICS (CFD) - Ahmad Hafizh Ridho; Eko Julianto; I Putu Arta Wibawa (Politeknik Perkapalan Negeri Surabaya, 2020)
Simulation on towing tank that require large costs, makes the ship’s owner have to pay moreto find their ship resistance value. Computational Fluid Dynamics (CFD) can be the substitution todetermine the resistance. This research discuss the effect caused by the variations application in wavepiercing forms on the MV. Saint John Paul II catamaran High-Speed Craft (HSC) at service speed tofind the smallest resistance value among them. The original model of the ship was obtained during TEEPresearch visiting program at National Taiwan University. 3D modeling on the wave-piercing variationswas using Rhinoceros6 software. Analysis to find the value of resistance was using CFD method withthe help of Orca3D and “SimericsMP+ForMarine” softwares. Variation was applied to the wavepiercing only, so it does not change the hydrostatic and stability of the initial model that has beenvalidated. Based on the transient CFD result at the speed of 38 knots, the researcher has obtained theaxe bow is having the smallest resistance value with 1101kN, followed by the raked bow, that have1126,35kN resistance value, and the original bow with 1137,7kN.